PENGARUH FIRM SIZE, DEBT RATIO DAN CAPITAL ADEQUACY RATIO TERHADAP PROFITABILITAS - Suryati, Diah; Yetti, Fitri (EQUITY, 2015)
This study examind the effect of firm size, debt ratio and capital adequacy ratio in the banking companies listed in Indonesia Stock Exchange (IDX) during 2011 - 2014. The methodology in this research is descriptive quantitative by using multiple regression analysis. This model is a statistical analysis tool that is used to describe the effect of independent variables on the dependent variable (partially and simultaneously). In partial results of the study concluded that the profitability of using formulas return on assets, the ratio of financial performance in banking that firm size has a positive and significant impact on profitability. And the debt ratio has a negative and significant impact on the profitability of the banking company. The higher firm size will lead to improved profitability in the banking company, the higher the debt ratio will cause a decrease in the profitability of the banking company. While the capital adequacy ratio has no significant effect on profitability. Simultaneously, the influence of three independent variables on profitability in the banking company is 30.5 percentage points.